Validation of a Rapid and Easy-to-Apply Method to Simultaneously Quantify Co-Loaded Dexamethasone and Melatonin PLGA Microspheres by HPLC-UV: Encapsulation Efficiency and In Vitro Release - Marco Brugnera; Marta Vicario-; Vanessa Andrés-Guerrero; Irene Bravo-Osuna; Irene Teresa Molina-Martínez; Rocío Herrero-Vanrell (MDPI AG, 2022)
This paper discusses the development and validation of a rapid method for the reversed phase HPLC-UV quantification of biodegradable poly(D,L-lactic-co-glycolic) acid (PLGA) microspheres co-loaded with two neuroprotective agents (dexamethasone and melatonin) (DX-MEL-MSs) to be intravitreally administered as a promising glaucoma treatment. The study was performed to validate two procedures that quantify the content of the two active substances entrapped into the polymer matrix during an encapsulation efficiency assay and the amount of drugs liberated over time during the in vitro release assay. The reversed-phase method allowed for the simultaneous determination of dexamethasone and melatonin, which were respectively detected at 240.5 and 222.7 nm. Chromatographic separation was performed using an Ascentis® C18 HPLC Column (25 cm × 4.6 mm, 5 µm) with an isocratic mobile phase composed of methanol-water (70:30, v/v) with 1.0 mL min−1 flow rate. The two procedures were validated analytically in terms of system suitability testing, specificity, linearity, precision, accuracy, sensitivity, and robustness. Both the validated procedures were applied to characterize DX-MEL-MSs and were found appropriate to quantify the drug quantities encapsulated and estimate their release profile over 10 days. The validation study designed in this work can be helpful for planning any other protocols that refer to the quantification of PLGA based drug delivery systems.